Determinants of sukuk’s liquidity level in Malaysia using latent liquidity measure - Wan Suhaimi, Wan Nurhanan (2014)
Subprime crisis in 2008 has surged the vital importance of a steady liquidity level in the market. Theoretically, Islamic financial market’s unique risk-sharing structure could provide some form of protection to its products and practitioners form being severely hit by the turmoil. Islamic bond, also known as sukuk, is the most popular component offered by the Islamic financial market. However, study on the liquidity level of sukuk in Malaysia shows a decreasing liquidity level by sukuk during the crisis period. The contradiction between the theory and actual figures provides a gap in knowledge, hence spurs this study to determine the drivers of sukuk liquidity level in Malaysia market and to possibly apprehend the pattern and preference of sukuk investors. We study the determinants of sukuk’s liquidity level in Malaysia bond market using a measure known as “latent liquidity”. The measure does not require much reliance on transaction data which makes it applicable to an illiquid market like Malaysia bond market. By utilising data from approximately more than 263 sukuk in Malaysia bond market, the study uses latent liquidity measure to examine the liquidity level of sukuk that maintain their trading activities throughout 2007-2012. The generated latent liquidity levels would then be used to determine the liquidity drivers for sukuk. Five bond characteristics (issuance amount, age, maturity, credit rating and coupon rate) are tested against sukuk’s latent liquidity level, with four characteristics (issuance amount, age, maturity and coupon rate) are found to be significantly related to sukuk’s liquidity level at 10% confidence level. On the other hand, the direction of correlation between issuance amount, maturity, age and credit rating variables towards liquidity is consistent with past literatures; issuance amount is positively related to liquidity while the other variables negatively correlated to liquidity. Sukuk investors’ preference to lock in buy-and-hold position in amortising the return and also their keenness to match their long term liability with sukuk are two imminent behaviours of sukuk investors concluded form the findings. Such findings are believed to provide better apprehension on sukuk investors’ behaviour and enable faster development in Malaysia Islamic financial system.